(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the frequency of micro organisms in open fractures of the extremities and their sensitivity pattern to the commonly used antibiotics. Methods: This descriptive study was conducted in the Department of Orthopaedic Surgery Nishtar Medical University Hospital Multan. The duration of our study extended from 29th June 2019 to 5th July 2020. Patients of either gender and age 18 to 60 years with open fractures meeting the inclusion criteria were enrolled in our study. Wound swabs were taken with Levine technique before surgical debridement and sent to laboratory for Gram staining and culture and sensitivity of the microbial agents. Post stratification comparison of important variables were done and P value was calculated with the help of Chi-square test. ( P<0.05 was considered statistically significant) Results: The total number of patients in our study were 195.Male patients were 161(82.6%) and female 34(17.4%). The mean age was 38.86±8.05 years. The most common fractured bone was tibia (20.5%, n=40) followed by humerus (19%, n=37%) and metacarpals/phalanges (16.9%, n=33). Gustilo Anderson type IIIA was the predominant type of fracture present in 71(36.4%) patients followed by type II (27.2%, n=53).Majority (62.6%, n=122) of the patients were presented to the hospital in time period extending from 6-12 hours of sustaining the injury. The culture report was positive in 187(95.8%) patients while no growth was noted in 8(4.1%) patients. Staphylococcus Aureus was reported in 112(57.4%) patients, Streptococcus in 34(17.4%) and E. Coli in 22(11.3%). Gram positive cultures were most sensitive to first generation Cephalosporin (60.5%, n=118) while Gram negative cultures to Quinolones (69.4%, n=25). Conclusion: Majority of open fractures of the extremities had positive culture of bacteria. Gram positive organisms were the most common isolated pathogens. First generation Cephalosporin was the most sensitive group of drugs against gram positive bacteria.